To the moon: Retail investor attention and sentiment across asset types in online media - Michael L. Smith; Nicole J. Olynk Widmar; Valerie Kilders (PLoS ONE, 2026)
Social media facilitates community building for users of varied and broad interests. Personal and retail (individual non-professional) investment communities have grown popular, and some engage in commentary on currencies and market events, while others coordinate action within markets. This analysis quantifies online and social media data about the US dollar and gold, as well as cryptocurrencies and stocks subject to attention shocks (including meme stocks), from 2020 through 2023. Using Quid’s social media listening platform, mentions of these four distinct topics were collected and analyzed separately to quantify the volume of mentions and sentiment of search results on a weekly basis. Statistical relationships between the asset groups and major events in the study period are explored; we assess public reactions to the regional bank failures, GameStop and AMC short squeeze events and the evolution of the crypto market. Large volumes of online media commentary on these topics suggest a sustained high level of interest in currency and investment markets, with evidence of the increasing influence of online communities in how the public views or talks about these markets.